2016
DOI: 10.1016/j.triboint.2016.05.043
|View full text |Cite
|
Sign up to set email alerts
|

The role of geometry changes and debris formation associated with wear on the temperature field in fretting contacts

Abstract: The temperature of a fretting contact is known to be a key factor in its development. However, as a test proceeds, the wear scar changes, both geometrically and through the formation of oxide-based debris-beds. Accordingly, the effects of these on the near-surface temperature field resulting from frictional heating in fretting has been analysed via numerical modelling. Under the test conditions examined, it was predicted that (i) the development of the wear scar geometry would result in a significant (up to ~ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…This corresponds to theoretical maximum flash temperature rise of less than 4 °C [49]. Another suggestion, from Jin et al [26], is that increased fretting frequency reduces the time for oxidation between interactions of the asperities in the contact. The authors consider this to be the most probable cause of this effect of frequency.…”
Section: Effect Of Frequency On Fretting Wear In Dry and Bo-lubricatesupporting
confidence: 55%
See 1 more Smart Citation
“…This corresponds to theoretical maximum flash temperature rise of less than 4 °C [49]. Another suggestion, from Jin et al [26], is that increased fretting frequency reduces the time for oxidation between interactions of the asperities in the contact. The authors consider this to be the most probable cause of this effect of frequency.…”
Section: Effect Of Frequency On Fretting Wear In Dry and Bo-lubricatesupporting
confidence: 55%
“…Fretting wear is a complicated process and studies have shown that frequency [18][19][20][21], slip amplitude [22][23][24], temperature [25][26][27][28][29][30][31][32], oxidation and oxygen supply at the surface [8][9][10][11][12], retention/ejection of debris from the contact [8,[13][14][15][16], contact pressure [33], tangential force, surface roughness [34][35][36][37] and hardness [13] of the contacting surfaces all play important roles in determining the severity of the fretting wear process. In practical systems often little can be done to change many of the above factors.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 13 shows that at 125°C, the scar surface which is evident following 500,000 cycles still has significant metallic character, which indicates that the oxide is being lost and reformed within the contact. Its inability to build a protective debris bed results from the shorter interpass time; this is despite the increase in contact temperature that will result from the higher frictional power dissipation at this frequency (estimated to be of the order of 70-150 K by Jin et al [5]), and indicates that the effect of the reduced inter-pass time dominates over that of the increased temperature. In addition, material build-up only appears at some positions along the wear scar, and it is much less significant compared to that observed in the low frequency test (see Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The temperature affects the progress of fretting via: (1) the mechanical properties of the bodies undergoing fretting; (2) the rate of oxide formation on the fretting surfaces; (3) changes to the way that oxide particles thus formed either are retained in the contact (and potentially develop into a glaze) or are expelled from the contact [3,4]. The fretting frequency can also affect these three influences as a result of: (1) temperature changes in the region of the contact due to the variation of the friction power dissipation; (2) changes in the time between interactions of an asperity in the contact (which will influence the oxidation of the nascent metal which takes place); (3) changes in the motion of debris particles and thus their retention in (or egress from) the contact [2,5]. Details of these three primary mechanisms of influence will now be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Fretting parameters have a great influence on the temperature field of the contact interface, but the temperature rise usually does not exceed 200 C. [24] In addition, Inconel 625 alloy has good structural stability below 650 C, and frictional heat generation is not enough to affect the behavior of Inconel 625, so the influence of frictional heat generation is not considered in this paper. Changes in the grain size, texture, and hardness of Inconel 625 are related to the deformation conditions (i.e., stress, strain, velocity, and temperature) during thermal compression.…”
Section: Discussionmentioning
confidence: 99%